Inflammation and Inflammasomes: Pros and Cons in Tumorigenesis - Liliana R. Balahura; Aida Selaru; Sorina Dinescu; Marieta Costache (Journal of Immunology Research)
Over the past decade, it has been well established that tumorigenesis is affected by chronic inflammation. During this event, proinflammatory cytokines are produced by numerous types of cells, such as fibroblasts, endothelial cells, macrophages, and tumor cells, and are able to promote the initiation, progression, and metastasis of different types of cancer. When persistent inflammation occurs, activation of inflammasome complexes is initiated, leading to its assembly and further activation of caspase, production of proinflammatory cytokines, and pyroptosis induction. The function of this multiprotein complex is not only to reassure inflammation and to promote cell death, through caspase activity, but also has been identified to have significant contributions during tumorigenesis and cancer development. So far, many efforts have been made in order to extend the knowledge of inflammasome implications and how its components could be targeted as therapeutic agents. Additionally, microRNAs (miRNAs), evolutionary conserved noncoding molecules, have emerged as pivotal players during numerous biological events by regulating gene and protein expression. Therefore, dysregulations of miRNA expressions have been correlated with inflammation during tumor development. In this review, we aim to highlight the dual role of inflammasomes and proinflammatory cytokines during carcinogenesis paired with the distinguished effects of miRNAs upon inflammation cascades during tumor growth and progression.